Implanting Religious Practices: Economic Behavior of Kemloko Tobacco Farmers - Muslich, Muslich (Shirkah: Journal of Economics and Business, 2018)
Tobacco from Kemloko Village has expressively attracted the attention of large companies such as Gudang Garam, Djarum, Sukun, Djambu Bol, Noroyono, and Bentoel. The Kemloko Village Community mostly works as a tobacco farmer, which is as many as 64.8% of total residents. In addition to these economic activities, the people of Kemloko Village are also active in carrying out traditional religious rituals (congregational prayers, tahlil dhikr and grave pilgrimage, ritual recitation, and slametan) led by village kyai. The kyai concurrently plays a role as important figures in the community, where the santri and society learn to adapt the outside realities, including the economic sphere. This article discusses the complex relationship of tobacco economic activity and the religious practices of the Kemloko Village community, arguing that the two factors makes traders (baskets and bosses) take advantage of the religious behavior of the elder kyai (as a source of authority) while the farmers get more profits. Keywords: tobacco farmers, religious practice, kyai, cultural brokerage